MOBILITAS MIGRAN PEDAGANG KAKI LIMA SUMATERA BARAT DI PASAR MANDAU DURI PROVINSI RIAU - Rini Wilmar; Siti Sofro Siddiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
A Migration is a population movement aimed to maintain from one place to another place exceed the limits of politics/country or part of administrative limits one of the countries. A Migration defines as a permanent movement from one area to another area. People who do migration called Migrant. This study is about “The Migrants mobility of west Sumatera retailers at Mandau Duri market in Riau Province”. The purpose of this study is to find out the push and pull factor of west Sumatera retailers at Mndau Duri market and also to find out a socio-economic situation of the migrants at Mandau Duri market. The method that used in this research is a qualitative research. A qualitative research is a research which revals the facts, situation and focused on social phenomena. The data collection technique used observation, questionnaire, interview and documentation techniquese based on the result, the number of the migrants of west sumatera retailers at Mandau Duri market was 300 vendors. From the interview result a researcher found the fact about the migrants incneased on income in the destination area rather than in the origin area. The migrant push factors is the family and williners aimed to change the life to be better.Keywords : Mobility, Migrant, West Sumatera, Retailes